2021
DOI: 10.3390/geosciences11060242
|View full text |Cite
|
Sign up to set email alerts
|

Toward Workable and Cost-Efficient Monitoring of Unstable Rock Compartments with Ambient Noise

Abstract: Ambient Vibration-Based Structural Health Monitoring (AVB–SHM) studies on prone-to-fall rock compartments have recently succeeded in detecting both pre-failure damaging processes and reinforcement provided by bolting. The current AVB–SHM instrumentation layout is yet generally an overkill, creating cost and power issues and sometimes requiring advanced signal processing techniques. In this article, we paved the way toward an innovative edge-computing approach tested on ambient vibration records made during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Seismological monitoring methods are thus useful to investigate and keep track of the mechanical state of potentially unstable sites. Several studies have shown the applicability of these methods to track the failure of rock columns (Levy et al 2011, Chiara Colombero et al 2021, Pierre Bottelin et al 2021, jointed rock masses , slope instabilities (Iannucci et al 2018, Dietze et al 2020, and the acceleration of clayey landslides (Mainsant et al 2012, Bièvre et al 2018, Fiolleau et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Seismological monitoring methods are thus useful to investigate and keep track of the mechanical state of potentially unstable sites. Several studies have shown the applicability of these methods to track the failure of rock columns (Levy et al 2011, Chiara Colombero et al 2021, Pierre Bottelin et al 2021, jointed rock masses , slope instabilities (Iannucci et al 2018, Dietze et al 2020, and the acceleration of clayey landslides (Mainsant et al 2012, Bièvre et al 2018, Fiolleau et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of this technique include non‐invasive, surface‐based sensor deployment, short‐term data acquisition, and rapid analysis of spectral attributes. Meanwhile, advancements in seismometer technology and the increasing availability of low‐cost instruments (Anthony et al., 2019; Ward & Lin, 2017) have improved the viability of ambient vibration measurements for rock slope instability characterization and monitoring across a range of settings (Bottelin et al., 2021; Colombero et al., 2021; Jongmans et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…in seismometer technology and the increasing availability of low-cost instruments (Anthony et al, 2019;Ward & Lin, 2017) have improved the viability of ambient vibration measurements for rock slope instability characterization and monitoring across a range of settings (Bottelin et al, 2021;Colombero et al, 2021;Jongmans et al, 2015).…”
mentioning
confidence: 99%
“…The geological materials must exhibit a high-level elastic parameter contrast to establish f o in a two-layer model (sediment-rock or a soft-soil layer over a compact or cemented half-space), meaning a marked difference in seismic impedance must characterize them. Currently, the HVSR technique is recognized for setting f o and fundamental periods of the ground [41][42][43][44][45], defining sediment thickness [18,19,46], and studying soil-structure interactions [15,47].…”
Section: Geophysical Methodsmentioning
confidence: 99%